A Modified Histopathologic Staging in Penile Squamous Cell Carcinoma Predicts Nodal Metastasis and Outcome Better Than the Current AJCC Staging. (August 2020) - Sali, Akash P.; Menon, Santosh; Murthy, Vedang; Prakash, Gagan; Bakshi, Ganesh; Joshi, Amit; Desai, Sangeeta B.
Abstract : Recently, the American Joint Committee on Cancer (AJCC) updated the staging system for penile squamous cell carcinoma. According to it, unlike its previous version, the involvement of urethra does not upstage the tumor; however, the involvement of corpora cavernosa (CC) does. The tumors involving CC are now staged pT3, whereas those involving corpora spongiosa (CS) are staged pT2, irrespective of the involvement of the urethra. In the current study, we sought to validate these recent modifications and in-process also attempted to improvise upon it. The histopathology slides were reviewed in 142 cases of penile squamous cell carcinoma. The histopathologic variables noted were tumor grade, anatomic level of invasion (CC/CS), lymphovascular invasion (LVI), and perineural invasion (PNI). Metastases to the lymph nodes were confirmed. Tumors were staged pT2/pT3 according to AJCC 8th edition and this staging system was further improvised by incorporating histopathologic variables similar to pT1 tumors in AJCC 8th edition. Accordingly, pT2 tumors invaded CS/CC without LVI or PNI and were not grade 3, whereas pT3 tumors invaded CS/CC, showed LVI and/or PNI, or were grade 3. Both the staging models were then correlated with nodal metastasis and disease-free survival. The new staging model ( P =0.001) and not the AJCC pT2/pT3 stages ( P =0.2) showed a statistically significant correlation with nodal metastasis. Similarly, only the proposed model significantly impacted disease-free survival ( P =0.011). To conclude, we were unable to validate the prognostic difference between the pT2/pT3 stages according to AJCC 8th edition. The staging system can be improvised by incorporating histopathologic variables similar to pT1 tumors.